PENINGKATAN KEMAMPUAN MEMBACA TELITI MENGGUNAKAN MODEL PEMBELAJARAN SQ3R BERBANTUAN MEDIA KOMUNANG - Maulida, Aula Zahirotul; Hidayati, Nur Alfin; Masfuah, Siti (Jurnal Pendidikan Dasar, 2025)
This research aims to determine student activity and close reading ability through the SQ3R model assited by KOMUNANG media in class V students ad SDN 4Karangrowo. SQ3R  is used to provide motivation for close reading. This model is applied in Indonesian language subjects in chapter 7 subchapter 2 regarding determining the main idea and main sentence of the explanatory sentence. The action hypothesis in this research is that the Implemention of the Learning I Model (SQ3R) Assited by KOMUNANG Media can increase student activity and close reading ability for class V SDN 4 Karangrowo. This type of research is classroom action research which will be carried out in class V of SDN 4 Karangrowo with research subjects of 23 students. This research took place over two cycles, each cycle consisting of four stages, namely the planning stage, implementation stage, observation stage, and reflection stage. The independent variable is SQ3R. The dependent variable is the ability to read carefully. The instruments used were interview sheets, evaluation questions, and observation sheets. The data analysis technique used is qualitative and quantitative data analysis. Student activity also increased in cycle 1 from 69% to cycle 2 to 94%. The ability to read carefully also increased in cycle 1 from 74% to cycle 2 to 84%.